Pelatihan Batik “Gesek Godhong”: Upaya Kemandirian Usaha bagi Anggota PCIA Hongkong - Eny Winaryati; Dodi Mulyadi; Eko Andy Purnomo; Endang Tri Wahyuni Maharani; Faqih Sulthan; Yusrin Yusrin (Universitas Muhammadiyah Semarang, 2024)
The Leadership the Aisyiyah Special Branch of Hong Kong, is an Aisyiyah association in Hong Kong. This Community Service Activity is driven by the desire of migrant workers to be more adequately prepared for their post-employment period. The hope is that Indonesian Migrant Workers (PMI) can be independent when they leave PMI and return to Indonesia with the soft skills of making Gesek Godhong. The choice of “Gesek Godhong” training is because the materials for making “Gesek Godhong” are easy to obtain and available in nature The creation of “Gesek Godhong” batik is a skill in producing environmentally friendly batik artwork. It can be made easily yet results in art pieces with high market value. The synergy between the Service Team from the Faculty of Education and Humanities (FIPH) at Universitas Muhammadiyah Semarang and PCIA Hong Kong is hoped to continue sustainably, providing a positive impact especially for migrant workers in Hong Kong. The survey results show that the “Gesek Godhong” batik training was highly effective and well-received, providing participants with the skills and knowledge to create environmentally friendly and high-value batik artwork. The hope for the future is that this training can be conducted after the migrant workers return to Indonesia.